Trade, investment and fragmentation of the global market : is Latin America lagging behind? - Kosacoff, Bernardo (ECLAC Buenos AiresAR, 2008)
Analyzes Latin America's insertion into the international economy and into the global value chains (GVC) phenomenon. Suggests that the current situation is unsatisfactory taking into consideration that some countries play a minor role in the GVCs while others, more inserted into them, show relatively small spillovers. Analyzes the factors behind these trends and draws some political lessons that might help improve the region's positioning in today's global scenario.